Comparative Analysis of Color Image Watermarking Technique in RGB, YUV, and YCbCr Color Channels - Koju, Roshan; Joshi, Shashidhar Ram (Nepal Journal of Science and Technology, 2015)
Since there are a number of color spaces, it has always been a big question to choose one for watermarking. The aim of this work is to find out better color space, among the frequently used one, under the same condition. Comparative performance analysis of color image watermarking technique in color channels of RGB, YUV, YCbCrcolor spaces was studied. For this purpose, color channels were watermarked using single level discrete wavelet transform-singular value decomposition (DWT-SVD). PSNR, and SSIM were used to test the imperceptibility of watermarked images. PSNR and NCC were used to measure the similarity of extracted and original watermarks.The maximum recorded PSNR value is 62.372 for R channel of RGB color space with SSIM value equal to 0.9709. Color channels of YCbCr color space were observed to be more robust and transparent as watermark image is best recovered from YCbCr color space with NCC values in the range 0.86 to 0.877 and SSIM values in the range 0.546to 0.554 under various geometric attacks. DOI: http://dx.doi.org/njst.v15i2.12130 Nepal Journal of Science and Technology Vol. 15, No.2 (2014) 133-140